INVENTORY MANAGEMENT SYSTEM FOR PRODUCTION PROCESS IN RUANG GEBYOK - Kristianti, Steffi; Andry, Johanes Fernandes (Jurnal Teknoinfo, 2024)
Jepara has been known as a carved city in foreign countries since hundreds of years ago. Woodcut furniture has been made in Jepara since Hindu, Islamic, and colonial times and is still made today. To maintain the tradition as a producer of Indonesian-style furniture, many Jepara residents choose to work traditionally by becoming craftsmen in the wood carving business. Ruang Gebyok has been in business since 2018 in Jepara, Central Java. Ruang Gebyok is engaged in the sale of furniture. This means records of stock data and transaction data are needed to create sales reports. However, the recording is still done manually in the book, so it can cause errors in stock data and financial calculations, even resulting in the loss of data. Custom goods transactions are made by customers via WhatsApp, so the owner needs a medium to convey customer orders. The advancement of the industrial revolution has forced automation on traditional business operations, especially in the furniture sector. So, the solution that can be proposed is a website-based inventory application for Ruang Gebyok to help with its management. The application is proposed in the form of a website because the owner often leaves the warehouse to install furniture. Waterfall is the design methodology used in this study. The stages of the waterfall method are analysis, design, coding, testing, implementation, and maintenance. The result is the application and the features in it needed by Ruang Gebyok, namely recording supplier data, raw material data, stock data for goods that are ready stock, purchase transactions for goods that are ready stock, purchase transactions for custom ordered goods, and combined sales reports of ready stock and custom foods that have previously been input as sold on the transaction page.